Engineering Vibration, Communication and Information Processing ICoEVCI 2018, India - Ray, Kanad; Sharan, S. N.; Rawat, Sanyog; Jain, S. K.; Srivastava, Sumit; Bandyopadhyay, Anirban; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses the revolution of cycles and rhythms that is expected to take place in different branches of science and engineering in the 21st century, with a focus on communication and information processing. It presents high-quality papers in vibration sciences, rhythms and oscillations, neurosciences, mathematical sciences, and communication. It includes major topics in engineering and structural mechanics, computer sciences, biophysics and biomathematics, as well as other related fields. Offering valuable insights, it also inspires researchers to work in these fields. The papers included in this book were presented at the 1st International Conference on Engineering Vibration, Communication and Information Processing (ICoEVCI-2018), India.
Chapter 1: Temporomandibular Joint Syndrome Prediction Using Neural Network -- Chapter 2: Optimization of AlGaN QW Heterostructure for UV Applications -- Chapter 3: Experimental Performance Evaluation of Cloud Servers in Ad Hoc Cloud Network -- Chapter 4: Analyzing Performance of Apache Pig and Apache Hive with Hadoop -- Chapter 5: Characterization of path loss for VHF terrestrial band in Aizawl, Mizoram (India) -- Chapter 6: A Comparative Performance Evaluation of Beamforming Techniques for a 2 x 6 Coaxial Cavity Horn Antenna Array for MELISSA -- Chapter 7: The impacts of exposure to low frequencies in the human auditory system - a methodological proposal -- Chapter 8: Behavior of Single Pylon of Air Cooled Con-denser Support Structure under Seismic and Wind forces -- Chapter 9: Rice Moisture Detection Based on Oven Drying Technique Using Microstrip Ring Sensor -- Chapter 10: A Novel Method to Smart City Water Management System with IoT devices and sensor device through Arduino -- Chapter 11: A Novel Fabric Adhesive UWB Magneto-Electric Dipole Antenna -- Chapter 12: Experimental Investigation using Laser Vibrometer and Finite Element Modeling for Modal Analysis of Cam Shaft -- Chapter 13: Performance Evaluation of Cognitive Internet of Things in Asynchronous Distributed space Time Block Codes over Two Wave Diffuse Power -- Chapter 14: Wavefunctions and Optical Gain in 〖〖In〗_(0.3) Ga〗_(0.7) As/Ga〖As〗_(0.4) 〖Sb〗_(0.6) Type-II Double Quantum Well Nano-heterostructure under External Uniaxial Strain.
Keywords: Telecommunication; Multibody systems; Vibration; Mechanics, Applied; Neural networks (Computer science) .; Electric power production; Communications Engineering, Networks; Multibody Systems and Mechanical Vibrations; Mathematical Models of Cognitive Processes and Neural Networks; Electrical Power Engineering